The Two Sides of the Coin: Religious Discourse Analysis of YouTube Videos Related to Aasia Bibi’s Blasphemy Case and Acquittal - Sufia Sultana (Linguistics and Literature Review, 2019)
The paper examines the discursive practices of religious discourse constructing devout religious identity that instigates fiery sentiments not only to rule out law of the state but also to assassinate others in the name of Allah (Hussain, 2018.). The religious discourse analysis is the framework and methodology of the paper. Religious polemics are categorized on the basis of spirituality present in them in contrast to the political discourse that constructs the rule of power. For analysis of the religious discourse on blasphemy case of Aasia Noreen Bibi, five speeches of the prominent religious figures of right and left wing have been selected and analysed on the basis of intertextuality for authenticity, affective, logic and lexical and syntactic construction to perpetuate the discursive practices in the realization and legitimization of the power of ideology of the actors through language. The paper delimits its scope to the case of Aasia Bibi, and the lives taken in reference to this case, i.e. assassination of the former governor of Punjab, Salman Taseer (Taseer’s Omen: Salman Taseer’s assassination shows how entrenched the religious right has become in Pakistan’s polity, 2011) and former minister of religious minorities Shahbaz Bhatti. The study focuses on the construction of an accusative, extremist, violent religious discourse employing abusive lexemes by some of the right winged scholars that led extremists to protest country wide and cause damage to the public property on hearing the Supreme Court’s acquittal of Aasia Bibi in October 2018 (Zafar, 2018; Hashim, 2018).